PERUBAHAN PEKERJAAN DI KABUPATEN KAMPAR SELAMA WABAH COVID-19: ANALISIS DEKOMPOSISI SEKTORAL - Mardiana; Dahlan Tampubolon; Bunga Chintya Utami; Tito Handoko (Bajang Institute, 2021)
The purpose of this study is to analyze the changes in employment that occurred due to the Covid-19 outbreak in Kampar Regency. The data used in this study is the State of the Workforce in Riau Province in August 2019 and 2020. Observations during that period were in accordance with the circumstances, where 6 (six) months before and after the Covid-19 outbreak entered Riau. Shift-share analysis is used to describe the shift in the employment structure of Kampar. Kampar Regency is still experiencing job growth during the Covid-19 outbreak, especially in the information and communication, services, trade and construction business fields. During the Covid-19 outbreak, the information and communication sector and other services had a positive industry mix and regional share. The agricultural and mining sector, although the regional share is minus, are helped by the positive industry mix. The trade, manufacturing, construction and educational services sectors have a negative industry mix but local factors are very helpful in increasing the number of local workers